Effect of agricultural subsidies on heterogeneous farmers’ fertilizer application intensity and its mediating mechanism: Based on China household finance survey database - He, Guoping; Feng, Jie; Xiao, Taofen (Frontiers in Environmental Science, 2022)
Agricultural subsidies have an important effect on the farmer’s fertilizer application behavior, but the differences in the effect on different farmers and its mediating mechanism have not been sufficiently studied. Using relevant data from the CFHS database in 2015, this paper focused on the differences in the effect of agricultural subsidies on fertilizer application intensity among farmers with different operation scales and planting structures, as well as the mediating mechanism of the effect of agricultural subsidies on farmers’ fertilizer application intensity. It was found that agricultural subsidies in general helped farmers reduce fertilizer application. This finding still held after replacing the explanatory variables. However, the effect of agricultural subsidies on fertilizer application intensity varied significantly across farmers with different operation scales and planting structures. The fertilizer reduction effect of agricultural subsidies was weakened by the increase in the operation scale and the share of food crop cultivation, i.e., the fertilizer reduction effect of agricultural subsidies on smaller farmers and cash crop cultivation was greater relative to larger farmers and food crop cultivation. Farmers' operation scale, planting structure and farm machinery inputs are important mediating variables of the effect of agricultural subsidies on farmers' fertilizer application intensity. The agricultural subsidies played a role in reducing fertilizer application intensity by encouraging farmers to expand their operation scale and increase food crop cultivation, and increased fertilizer application intensity by incentivizing farmers to purchase farm machinery and adopt mechanical farming. Finally, some suggestions were put forward to play the fertilizer reduction effect of agricultural subsidies based on the findings of the study.